PELAKSANAAN PERATURAN DAERAH TENTANG PENGELOLAAN RUMAH KOS DALAM MENDUKUNG PEMBANGUNAN DAERAH KABUPATEN BADUNG - Manuaba, Ida Ayu Sintya Naraswari; I Gusti Agus Yuda Trisna Pramana (Universitas Tabanan, 2025)
The boarding house is one business that is growing in District Badung an option a temporary residence for migrants who intend to work and study. Everyone who owns a boarding house in the District Badung regency must have license this boarding house management to provide legal certainty, realizing the boarding house decent, safe and comfortable in accordance with its function, protect the interests of all parties, create peace and public order in society. The implementation of licensing through the Online Licensing Service (LAPERON) has not accommodated services for obtaining boarding house management license, so there is a need for certainty from the Regional Regulation District Badung Number 24 of 2013 concerning Boarding House Management regarding the obligation for managers to have a boarding house management license. Writing this using empirical legal research methods approach the facts and law approach with data collection interviews. The results obtained in this study show that the management's obligation to have a boarding house management license is not implemented based on the provisions stipulated in Regional Regulation Number 24 of 2013 concerning Boarding House Management, so that there are obstacles faced by law enforcers to control management permits boarding house.